Review on Composite Joints for Cold-Formed Steel Structures - Faisal, Amsyar; Cher Siang, Tan; Chau Khun, Ma; Arizu, Sulaiman (EDP Sciences, 2018)
Introduction of the lightweight cold-formed steel (CFS) sections to building construction has been well-established these days due to its high structural performance, corrosion resistance, ease of construction and maintenance as well as aesthetic appearance. In the early of 21th century, researchers found out that the structural performance of the CFS can be improved significantly by integrating it with other materials, for instance, concrete, to create the composite system. This is due to concrete material is excellent in compression but less effective to resist tension force. There were little works being carried out and lack of technical literature regarding on the composite connections for CFS structural frames, especially on the composite beam-to-column joints. This paper aims to collect and review on the previous researches of composite joints for CFS structures from the past two decades. The review is made in three distinctive topics i.e. CFS beam-to-column joints, composite beam-to-slab joints and composite beam-to-column joints. Most of the investigations indicated that composite joint yields higher ultimate load and moment resistance compared to the non-composite joint.